2004
DOI: 10.1103/physrevb.69.075309
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of strontium on Si(001)

Abstract: This paper reports state-of-the-art electronic structure calculations on the deposition of strontium on the technologically relevant, (001) orientated silicon surface. We identified the surface reconstructions from zero to four thirds monolayers and relate them to experimentally reported data. A phase diagram is proposed. We predict phases at 1/6, 1/4, 1/2, 2/3 and 1 monolayers. Our results are expected to provide valuable information in order to understand heteroepitaxial growth of a prominent class of high-K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
87
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 50 publications
8
87
1
Order By: Relevance
“…In this way electronic defects such as broken bonds can be identified. The interface involving silicon (Si) and strontium titanate (SrTiO 3 ) [37] is the example that has been recently studied [2,16]. It was found that a specific coverage of one half monolayer of Sr atoms will chemically saturate the silicon substrate (leaving no dangling bonds), as the left panel of Figure 13.…”
Section: Computational Design Of Semiconductor Interfacesmentioning
confidence: 97%
See 1 more Smart Citation
“…In this way electronic defects such as broken bonds can be identified. The interface involving silicon (Si) and strontium titanate (SrTiO 3 ) [37] is the example that has been recently studied [2,16]. It was found that a specific coverage of one half monolayer of Sr atoms will chemically saturate the silicon substrate (leaving no dangling bonds), as the left panel of Figure 13.…”
Section: Computational Design Of Semiconductor Interfacesmentioning
confidence: 97%
“…Neither the chemically saturated interface nor the dependence of the insulating behavior on the stoichiometry at the interface could have been addressed using classical, interatomic potentials. Further discussions may be found in references [2,16,17]. …”
Section: Computational Design Of Semiconductor Interfacesmentioning
confidence: 99%
“…The main reason why STO is not considered as a viable gate dielectric is that its electron injection barrier in the structures prepared so far is too small for transistor applications [4]. Nevertheless, ab-initio calculations [5,6] provide strong evidence that the band offset can be engineered to meet technological requirements. Besides perovskite oxides, films with fluorite derived structures are considered promising candidates for epitaxial high-k oxides on silicon [7,8].…”
mentioning
confidence: 99%
“…We have used a regular mesh corresponding to 36 k-points per (1 × 1) surface unit cell. Further details about the computational procedure can be found in our previous publications in this field [5,6,24,25].…”
mentioning
confidence: 99%
See 1 more Smart Citation